Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Kualitas Pelayanan Hotel - Claudius Dharu Aji Wicaksono; Henry Yuliamir (Mahesa Research Center, 2026)
This article aims to analyse the role of human resource management in improving hotel service quality. The problem focuses on how recruitment, training, performance appraisal, and reward systems contribute to shaping employee service behaviour and guest experience. To approach this issue, the study draws on Human Capital theory, Strategic Human Resource Management, and service quality concepts. Data were collected through in-depth interviews, observations, and document analysis, and were analysed qualitatively using a case study approach. The study concludes that effective HRM practices are characterised by value-based recruitment, continuous training, and performance evaluation and reward systems based on service behaviour, which directly shape proactive, empathetic, and responsive employee attitudes. The empirical findings indicate that service consistency is more influenced by the internalisation of values and organisational culture than by procedural aspects alone. The novelty of this study lies in the integration of strategic HRM approaches and service behaviour formation in a cross-cultural context, resulting in a conceptual model linking HRM practices, employee behaviour, and guest experience.